Multilateral environmental agreements in the WTO: Silence speaks volumes - Henrik Horn; Petros C. Mavroidis (Research Institute of Industrial Economics (IFN), 2013)
This study contributes to the debate concerning the appropriate role of multilateral environmental agreements (MEAs) in in WTO dispute settlement. Its distinguishing feature is that it seeks to address this relationship in light of the reason why the parties have chosen to separate their obligations into two bodies of law without providing an explicit nexus between them. The basic conclusion is that legislators' silence concerning this relationship should speak volumes to WTO adjudicating bodies: MEAs should not be automatically understood as imposing legally binding obligations on WTO Members, but could be used as sources of factual information.
Keywords: F13; K32; K33; Q56; 330; WTO; dispute settlement; environmental agreements